Perancangan dan Pembangunan Website Manajemen Kas pada BUMDes Megamendung Jaya - Faldi Azwar; Choirul Anwar; Ayatulloh Michael Musyaffi (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to design and develop a web-based cash management system for BUMDes Megamendung Jaya, a village-owned enterprise in Bogor Regency, West Java, that manages five business units: a health clinic, a coffee house, a tourism division, camping-equipment rental, and an internet service unit. The problem addressed is that cash recording is still performed manually and separately across units, causing input errors, delayed reporting, and limited public access to performance information. This study applies a Research and Development (R&D) method using the System Development Life Cycle (SDLC) with a Waterfall model, covering requirements analysis, system design, implementation, testing, and evaluation. Data were collected through observation, interviews with the BUMDes director, and documentation of existing cash-recording formats. The system was built with PHP (Laravel), Bootstrap, and MySQL, and produces cash receipt and disbursement records, automatically generated cash reports referring to the Financial Accounting Standards for Private Entities (SAK EP), and a public performance dashboard.